3-Deoxyglucosone reduces glucagon-like peptide-1 secretion at low glucose levels through down-regulation of SGLT1 expression in STC-1 cells. (4th July 2021) - Zhou, Liang; Wang, Fei; Song, Xiudao; Shi, Min; Liang, Guoqiang; Zhang, Lurong; Huang, Fei; Jiang, Guorong
Abstract: Context: Sodium glucose co-transporter 1 (SGLT1) triggers low glucose-induced glucagon-like peptide-1 (GLP-1) secretion. We reported that a two-week administration of 3-deoxyglucosone (3DG), an independent factor associated with the development of pre-diabetes, reduces basal GLP-1 secretion in rats. Objective: This study investigated the effects of 3DG on GLP-1 secretion and SGLT1 pathway under low-glucose conditions in STC-1 cells. Methods: STC-1 cells were incubated with phloridzin or 3DG at 5.6 mM glucose. SGLT1 expression (by western blotting), GLP-1 and cyclic adenosine monophosphate (cAMP) levels (by ELISA), and intracellular Ca 2+ concentration (by Fluo-3/AM) were measured. Results: Phloridzin inhibited GLP-1 secretion. SGLT1 protein expression in STC-1 cells cultured in 5.6 mM glucose is higher than that in 25 mM glucose. Exposure to 3DG for 6 h reduced GLP-1 secretion, SGLT1 protein expression, and intracellular concentrations of cAMP and Ca 2+ . Conclusions: 3DG reduces low glucose-induced GLP-1 secretion in part through reduction of SGLT1 expression.